PERSEPSI SISWA TERHADAP KOMPETENSI PROFESIONALISME GURU KEAHLIAN JASA BOGA SMK NEGERI 1 PAINAN - Rahmawati, Intan; Yusuf, Liswarti; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2013)
The purpose of this for study was to identify and describe how students perceptionts of teacher professional competence skills catering services SMK Negeri 1 Painan. This resereach is quantitative descriptive. The populations consist 0f 90 people namely grate students X, XI, and XII SMK Negeri 1 Painan. Based on the result of this study concluded that: 35% of respondents had the perception that the teacher is good mastery of the material, 33% of respondents had the perception that the teacher is good management of teaching and learning, 42% of respondents had the perception that the teacher is good classroom management and workshop, 43% of respondents had the perception that the teacher use of media to learn good teacher, 45% of respondents had the perception that the teacher the management of teaching and learnings interactions, and 43% of respondents had the perception that the teacher is good evaluation of learning achievement. The result showed that overall 43% of respondents students perceptions of teacher professional competence is very good category. Â  Keywords: perception, teacher professional competence